Efektifitas penerapan model pembelajaran kooperatif tipe students team achievement division dalam meningkatkan aktivitas dan hasil belajar kognitif siswa - Rahmat Saleh; Filawati (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2019)
The low activity and cognitive learning outcomes of Grade VIIIB MTs Aisyiyah students require innovation in learning by using cooperative learning models. This study aims to determine the increase in activities and learning outcomes in biology through the application of cooperative learning models of students team achievement division class VIIIB MTs Aisyiyah Sungguminasa Kab. Gowa. This type of research is Classroom Action Research which consists of two cycles. The subjects of the study were students of class VIIIB MTs Aisyiyah Sungguminasa Kab. Gowa. The research instrument was an observation sheet and a test. Data analysis techniques with qualitative descriptive statistical analysis for student activities and analyzed with quantitative descriptive statistical analysis for learning outcomes. The results showed that there was an increase in students' cognitive learning activities and outcomes namely from cycle 1 and cycle 2 with an average value of 46.71% and 85.5%. Thus, the conclusion of this research is the use of cooperative learning models of students team achievement division type can increase the activities and learning outcomes of students of class VIIIB MTs Aisyiyah Sungguminasa Kab. Gowa.